Erratum: Publisher's note: Relativistic and close-coupling effects in the spin polarization of low-energy electrons scattered elastically from cadmium (Physical Review Letters (2011) 107 (093202)) - Bostock, C.; Berrington, M.; Fursa, Dmitry; Bray, Igor (2011)
This paper was published online on 23 August 2011 with an incorrect reference citation. Reference [12] should read as “T. J. Gay, Adv. At. Mol. Phys. 57, 157 (2009)AAMOA20065-219910.1016/S1049-250X(09)57004-8.” The reference has been corrected as of 1 September 2011. The reference is correct in the printed version of the journal.